Ratio Methods Used to Determine the Value of Companies. Nature and Basic Features of “Price : Income” Ratio - Nenkov, Dimitar (Research Papers, 2007)
The selection and implementation of the appropriate investments for acquisition of going-concern enterprises is dependent to a very high extent upon the quality of their prior valuation. Three basic approaches for estimation of companies’ value are popular and broadly applied both in theory and practice: assets-based approach, income-based approach and relative-valuation approach. Each of them includes a number of specific methods of application. This study is about the relative methods for valuation of companies and the opportunities for their successful application in Bulgaria. The focus is put upon one of the most widely used multiples (ratios) – the price-earnings ratio.The technology, as well as the most important advantages and disadvantages of the multiples (relative) valuation are presented and discussed. Special attention is given to the key requirements, related to their proper use. The identification, justification and application of the right multiples require in-depth knowledge of the fundamental factors which determine their levels. In this regard a short review is made of the price-earnings ratios on different international markets, as well as analysis of their levels on the Bulgarian capital market. The essence and logic of the fundamental price-earnings ratios is also demonstrated in this paper, together with their interrelation with the actual price-earnings ratios.